(untitled) (Research, Society and Development, 2022)
Reading and vocabulary are widely regarded as essential to enhance reading comprehension in a second language. Therefore this study focuses on inserting English vocabulary into students to aid a number of EFL learners to improve their reading comprehension in a remote setting district public school located in Ecuador, where the lack of technological tools presents them. This study tries to explain the advantages of using explicit vocabulary guidelines in reading activities to improve reading comprehension in this group of young learners. The thirty-eight children were separated into two groups of nineteen students; each had six reading lessons. After the class, they completed in a reading comprehension quiz. The findings demonstrate that students had improved their reading comprehension after applying the explicit vocabulary instruction method on them, which mean is (M=7.17). Traditional methods, such as implicit vocabulary instruction, show lower reading comprehension in learners; the mean was ( M= 6.89). Other findings in this study demonstrate that girls had a better positive impact on their reading than boys. (31.6 %) girls were better in score in comparison with boys, who rose to (18.4%). Moreover, all the students recognized that in 5 months, they had learnt more English vocabulary words than in two years of classes out of campus. Thus their reading comprehension improved on them.